Self-templating synthesis of hollow NiFe hydroxide nanospheres for efficient oxygen evolution reaction. (10th October 2020) - Jia, Dandan; Gao, Hongyi; Zhao, Jie; Xing, Liwen; Chen, Xiao; Huang, Xiubing; Dang, Rui; Wang, Ge
Abstract: Hierarchical nanostructure with hollow feature can greatly promote electrocatalytic activity by facilitating the diffusion of active species and accelerating the contact between catalyst and electrolyte. In this paper, we report the preparation of hierarchical hollow NiFe hydroxide nanospheres assembled from ultrathin nanosheets as the OER electrocatalyst via a simple and gentle self-templating strategy, which includes two steps: the synthesis of Ni(OH)2 nanospheres precursor and its further transformation to the final hollow-spheres after the introduction of Fe 3+ via a mild hydrothermal method. The hollow NiFe hydroxide nanospheres were proven to be composed of ultrathin nanosheets which formed porous walls. This unique structure achieved numerous mass transfer channels for electrolytes, ideal pathways for ions and electrons, and a high specific surface area, leading to the improved performance for the product during the electrocatalytic reaction. In addition, the charge transfer rate and structural stability of the architecture have been greatly improved after the addition of Fe 3+, which guaranteed high electrochemical performance toward OER. The tafel plot for NiFe-190 without any conductive agents is 60 mV dec −1 and the overpotential needed to reach a current density of 10 mA cm −2 is a 270 mV.